THE MEASUREMENT OF EXCELLENT QUALITY SERVICE THROUGH WORK MOTIVATION AND DISCIPLINE OF EMPLOYEE (As empirical study at Balai PSDA Wilayah II Seputih Sekampung) - Karim, Mirwan (Universitas Muhammadiyah Metro Lampung, 2018)
This research uses an endogenous latent variable of excellent quality service and exogenous variable of work motivation and work discipline of employee at Balai PSDA Region II Seputih Sekampung. The purpose of this study is to determine the effect of work motivation and work discipline on the excellent quality service. The analytical tool used in this research is structural equation modelling analysis. Based on the result of calculation using analysis tool found that exogenous latent variable of work motivation has no direct positive effect on the exogenous variable of work discipline. The exogenous latent variable of work motivation has no direct positive effect on the endogenous variable of excellent quality service. The exogenous latent variable of work discipline has a direct positive effect on the endogenous variable of excellent quality service. The findings of the comparative research results of these two variables, explaining that exogenous latent variables of work discipline give greater influence than exogenous latent variable of work motivation toward endogenous variable of excellent quality service.Keywords: excellent quality service, discipline, motivation